Are Photographs Worth More Than a Thousand Words? Examining the Effects of Photographic–Textual and Textual-Only Frames on Public Attitude Toward Nuclear Energy and Nanotechnology - Lee, Edmund W. J.; Ho, Shirley S. (Journalism & mass communication quarterly, 2018)
This study examines the impact of photographic–textual and risk–benefit frames on the level of visual attention, risk perception, and public support for nuclear energy and nanotechnology in Singapore. Using a 2 (photographic–textual vs. textual-only frames) × 2 (risk vs. benefit frames) × 2 (nuclear energy vs. nanotechnology) between-subject design with eye-tracking data, the results showed that photographic–textual frames elicited more attention and did have partial amplification effect. However, this was observable only in the context of nuclear energy, where public support was lowest when participants were exposed to risk frames accompanied by photographs. Implications for theory and practice were discussed.